Epispadias and the associated embryopathies: genetic and developmental basis. Issue 2 (10th October 2016) - Suzuki, K.; Matsumaru, D.; Matsushita, S.; Murashima, A.; Ludwig, M.; Reutter, H.; Yamada, G.
Abstract : The abnormalities in the urogenital organs are frequently observed as human developmental diseases. Among such diseases, the defects in the upper part of external genitalia are rather rare named epispadias. The cleft in the dorsal part of external genitalia often reaches to the urethra. In general, the urogenital abnormalities accompany defects in the adjacent tissues and organs. The ventral body wall and bladder can also be affected in the patients with dorsal defects of the external genitalia. Therefore, such multiple malformations are often classified as bladder exstrophy and epispadias complex (BEEC). Because of the lower frequency of such birth defects and their early embryonic development, animal models are required to analyze the pathogenic mechanisms and the functions of responsible genes. Mutant mouse analyses on various signal cascades for external genitalia and body wall development are increasingly performed. The genetic interactions between growth factors such as bone morphogenetic proteins (Bmp) and transcription factors such as Msx1/2 and Isl1 have been suggested to play roles for such organogenesis. The significance of epithelial–mesenchymal interaction (EMI) is suggested during development. In this review, we describe on such local interactions and developmental regulators. We also introduce some mutant mouse models displaying external genitalia‐body wall abnormalities. Abstract : Epispadias and the associated embryopathies; the candidate signal cascades for caudal embryonic development